Pengaruh CSR, Profitabilitas dan Kebijakan Deviden Terhadap Nilai Perusahaan BUMN Terdaftar di BEI - Slamet Maryoso; Dian Indah Sari (LPPM Universitas Bina Sarana Informatika, 2023)
Abstract This study aims to determine the effect of Corporate Social Responsibility, profitability, dividend policy on the value of BUMN companies listed on the Indonesia Stock Exchange for the 2017-2020 period. quantitative descriptive as this type of research. The data collection method is literature study where data is obtained from journals, books and literature related to the research title. This study uses the Classical Assumption Test as a data analysis technique. The conclusions in this study include: 1. Corporate Social Responsibility has a significant effect on the value of BUMN companies listed on the IDX for the 2017-2020 period. 2. Profitability has a significant influence on company value in state-owned companies listed on the IDX for the 2017-2020 period. 3. The dividend policy does not have a positive and significant impact on the value of BUMN companies listed on the IDX for the 2017-2020 period. 4. Corporate Social Responsibility, profitability and dividend policy together have a significant influence on the value of BUMN companies listed on the IDX for the 2017-2020 period.